Analisis Profil Senyawa Metabolit Sekunder Ekstrak Daun Cempedak (Artocarpus integer) Dengan Metode Spektrofotometer UV-Vis dan LC-MS: Analysis Of Secondary Metabolites Compound Profile Of Cempedak Leaf Extract (Artocarpus integer) Using Uv-Vis Spectrophotometer And LC-MS Methods - Hariri Putri, Maudina Artha; Tilarso, Dara; Sari, Tri Anita (Jurusan Farmasi Poltekkes kemenkes Makassar, 2025)
Cempedak (Artocarpus integer) leaves contain secondary metabolite compounds including flavonoids, saponins, phenolics, terpenoids, and tannins that act as natural antioxidants for anti-aging. The purpose of this study is to determine the metabolite compounds in ethanol extract of cempedak leaves analyzed using the LC-MS method. The results of analysis using the LC-MS method on cempedak leaf extract were 103 compounds consisting of flavonoids 92.44543%, phenols 3,66556%, saponins 1.50683%, alkaloids 1.22696%, terpenoids 0.98201%, tannins 0.41495% and steroids 0.22850%. The results on the chromatogram of the liquid chromatogram at the highest peak with the identified compound composition of 1.88812% called serotonin D belongs to the flavonoid group having a molecular weight (m/z) of 676,2308 with the chemical formula C40H36O10. These results show that cempedak leaves using the LC-MS method contain flavonoids, phenols, saponins, alkaloids, terpenoids, tannins, and steroids.